(untitled) (Research, Society and Development, 2021)
Our intention is to examine, through the analysis of the Book of Virtuous Wisom of D. Pedro (1392-1449), how the genre of the Mirrors of Princes appeared in Portugal in the context of the House of Avis (1385-1580) , when designing an ideal ruler. In view of the 15th century as the period in which the ideas of the Italian Renaissance inspired by classical antiquity began to enter the Portuguese court, with the introduction of works of a civic and pedagogical nature, we organize the text to understand the characteristics present in this treaty of the valorization of human capacities, especially in the field of Education. To carry out this research, the methodology starts from the assumptions of bibliographic and documentary research, using the contributions of Social History.